2022-RA-774-ESGO The follow-up of patients with high risk of ureteric postoperative complications – presentation of our prophylactic method. (20th October 2022) - Mrugała, Maja; Borowiec, Zofia; Nowak, Krzysztof; Fiutowski, Marek; Kasperski, Mariusz; Milnerowicz-Nabzdyk, Ewa; Kalus, Marcin
Abstract : Introduction/Background: The objective was to explore our method of prophylaxis and detection of elevated risk of ureteric postoperative complications after laparoscopic radical hysterectomies in the Oncology Centre Opole (OCO), Poland performed in the years 2020–2022 Methodology: All women underwent radical hysterectomy for benign (deep infiltrating endometriosis, DIE) or malignant (endometrial or cervical cancer) indications. All DIE patients had external infiltration of the ureter or rigid adhesions. The visual functional assesment of the ureter and the ICG-vascularisation check was performed to detect the high risk patients. In case of any risk factor of ureteric postoperative damage the cystoscopic procedure of JJ-stenting was performed. The prolonged JJ stent maintaining, for up to 3 months, was obligatory. After the JJ stent removal, the cystoscopic evaluation was performed and patients were qualified to the follow up group or in case of any serious postoperative complication, the laparoscopic reoperation was planned and performed the next day. Results: Of all women undergoing radical hysterectomy, the high risk group consisted of 50 patients, all had JJ stenting of one or both ureters. Amongst them there were 5 ureteric injuries: 3 mecanical injuries, 2 ureteral tumor removal. All patients had the complete dissection of the ureter down to the ureteric canal. The reparation procedures consisted of 3 ureter retransplantations, 2 Boari flap procedures, 1 bilateral uretero-ileo-cystoneostomy. There was no ureteric postoperative complications reported in the group without JJ-stenting intervention. Diagnosis of the injury or risk of the injury was always set during the operation time and none of them was delayed. In the rest of patients no intervention was necessary. Conclusion: Immediate identification of the high risk patients and prolonged stenting of ureters allow the instantaneus repair of ureteral complications in patients who need it.